2019
DOI: 10.1093/femsec/fiz128
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical patterns in soil bacterial communities across the Arctic region

Abstract: The considerable microbial diversity of soils and key role in biogeochemical cycling have led to growing interest in their global distribution and the impact that environmental change might have at the regional level. In the broadest study of Arctic soil bacterial communities to date, we used high-throughput DNA sequencing to investigate the bacterial diversity from 200 independent Arctic soil samples from 43 sites. We quantified the impact of spatial and environmental factors on bacterial community structure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 67 publications
(82 reference statements)
9
57
0
Order By: Relevance
“…In this study, the soil water content was identified as the main factor affecting the diversity of soil bacterial community structure, similar to previous reports on the effects of water stress on soil bacterial communities [55,71,72]. Moreover, the pH was also found to be an important factor affecting the diversity of soil bacterial communities, a result that was also similar to other studies [73][74][75][76][77][78]. Previous experiments have illustrated that pH is a good predictor of spatial distribution at Changbai Mountain [74], in the Arctic [73,78], at the continental-scale [75], and on the global atlas [77].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the soil water content was identified as the main factor affecting the diversity of soil bacterial community structure, similar to previous reports on the effects of water stress on soil bacterial communities [55,71,72]. Moreover, the pH was also found to be an important factor affecting the diversity of soil bacterial communities, a result that was also similar to other studies [73][74][75][76][77][78]. Previous experiments have illustrated that pH is a good predictor of spatial distribution at Changbai Mountain [74], in the Arctic [73,78], at the continental-scale [75], and on the global atlas [77].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the pH was also found to be an important factor affecting the diversity of soil bacterial communities, a result that was also similar to other studies [73][74][75][76][77][78]. Previous experiments have illustrated that pH is a good predictor of spatial distribution at Changbai Mountain [74], in the Arctic [73,78], at the continental-scale [75], and on the global atlas [77]. However, no significant relationships between soil bacterial communities and other soil physicochemical properties were identified.…”
Section: Discussionsupporting
confidence: 85%
“…Biogeographical patterns have been identified in the phyllosphere of other tree species [15,80]. However, few studies have examined the biogeographical patterns of different microbial populations in the phyllosphere (e.g., rare versus abundant and core versus non-core taxa) as in other environments [16,45,81]. Our results revealed that biogeographical patterns were strongest in non-core taxa, exhibiting a non-random distribution across space and environmental gradients that contrasted with the cosmopolitan distribution of the relatively dominant core microbiome.…”
Section: Biogeographic Patterns Differ Between Core and Non-core Membmentioning
confidence: 99%
“…In this study, we used a high-throughput next-generation sequencing approach. Generally, Arctic bacterial communities seem to be dominated by different taxa than other biomes, likely reflecting the impact of polar environmental conditions on microbial communities (Malard et al 2019). Tundra soils are generally characterized as poorly enriched by organic matter, over-saturated and poorly aerated.…”
Section: Microbiome Composition and Its Relationship With Soil Propermentioning
confidence: 99%